(untitled) (ENTHYMEMA, 2025)
The article focuses on the representation of the villa in the surroundings of Florence in The English Patient (1992) by Michael Ondaatje, where four characters from different countries find themselves living together for a brief period at the end of World War II. It is a precarious space of reconfiguration of identities traumatized by the conflict, beautifully frescoed yet half-destroyed, strewn with unexploded mines. The fragile community that gathers around the English patient is finally scattered after the bombing of Hiroshima and Nagasaki. The historical and intertextual quality of the text develops geographically: the space of the villa overlaps with the North African desert, to which the protagonist’s past is linked. The analysis of the building, which functions as a transitional place of healing and recovery, as a paradise, but also a hell of desolation and death, allows us to investigate some crucial questions of the postcolonial and transnational contemporary world.